Gender Differences in Diabetes Self-Management: A Mixed-Methods Analysis of a Mobile Health Intervention for Inner-City Latino Patients. (January 2013) - Burner, Elizabeth; Menchine, Michael; Taylor, Elena; Arora, Sanjay
Background: The benefit of mobile health (mHealth) on diabetes management among low-income, inner-city patients is largely unknown, particularly for Latino patients. TExT-MED (Trial to Examine Text Message for Emergency Department Patients with Diabetes) is a text message-based program designed to improve disease knowledge, self-efficacy, and glycemic control among low-income, inner-city Latinos. In phase I, 23 patients participated in an acceptability and feasibility study. Contrary to our model, there was no increase in knowledge despite increases in self-efficacy and healthy behaviors. In phase II, we performed a mixed-methods analysis to understand how TExT-MED achieved these seemingly contradictory findings. Method: We performed a qualitative analysis of focus groups with patients from phase I. We explored patients' receipt of health information from TExT-MED and other information sources. We used these qualitative findings to perform a mixed-methods analysis of the outcomes from phase I, reanalyzing the quantitative measures of self-efficacy, diabetes knowledge, and healthy behaviors. Results: We conducted two focus groups, one in English and one in Spanish. Through qualitative analysis, we found gender differences in information sources, dietary self-efficacy, and desired educational content. Applying this knowledge, we re-stratified phase I outcomes by gender and found differential changes in diabetes knowledge, self-efficacy, and behaviors. Men had increased self-efficacy while women showed increased knowledge. Conclusions: The efficacy of mHealth on diabetes management was affected by gender. Specifically, men and women differ in their dietary self-efficacy, information sources, and desired topics in future mHealth interventions. To achieve maximal impact, future mHealth interventions should be mindful of this gender difference.